ChemInform Abstract: Et3B‐Mediated Radical‐Polar Crossover Reaction for Single‐Step Coupling of O, Te‐Acetal, α, β‐Unsaturated Ketones, and Aldehydes/Ketones. Issue 8 (25th February 2014) - Kamimura, Daigo; Urabe, Daisuke; Nagatomo, Masanori; Inoue, Masayuki
Abstract The mixed O, Te‐acetal (I) derived from 2, 4, 10‐trioxaadamantane reacts with cyclic α, β‐unsaturated ketones (II) under Et3B/O2‐mediated radical conditions to form the β‐adducts (III).